PENINGKATAN KETERAMPILAN MENULIS TEKS DESKRIPSI MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE GALLERY WALK BERBANTUAN MEDIA FLASHCARD PADA MURID KELAS VII SMP NEGERI 7 MADIUN - Layly Shari Ramadhani, Nur; Kuncoro Hadi, Panji; Budiharto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the Gallery Walk cooperative learning model assisted by flashcards and to determine the improvement in students’ descriptive writing skills following the implementation of this model. The approach used was Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which was conducted over two cycles. The research subjects consisted of 32 seventh-grade students at SMP Negeri 7 Madiun. Data collection techniques included observation, testing, and documentation. Data analysis was conducted using both quantitative and qualitative methods. The results of the study indicate that the implementation of the Gallery Walk cooperative learning model supported by flashcards was able to improve students’ descriptive writing skills. The average writing skill score increased from 67.4 in the pre-cycle to 75.2 in Cycle I and in Cycle II rose to 83.7. In the pre-cycle, the percentage of students meeting the standard also increased from 34.4% (11 students), and in Cycle I it rose to 65.6% (21students), and in Cycle II, it reached 100% (32 students). The implementation of this model also encouraged students to actively exchange ideas, collaborate, discuss, and provide feedback to one another. Thus, the “Gallery Walk” cooperative learning model, supported by flashcards, is effective in improving the descriptive writing skills of seventh-grade students at SMP Negeri 7 Madiun.